Fecundity of «chiochio» Psectrogaster rutiloides (Pisces: Curimatidae) in Ucayali, Peru - Zaldívar R., Javier (2012)
Studies on the potential fecundity of chiochío, Psectrogaster rutiloides, are scarce despite this is one of the main fish species for small scale commercial and subsistence fishing catch in the Ucayali basin (Peru). A total of 74 female specimens on maturity stage IV were collected in October and November 2009. Total length, body weight, and gonad weight were recorded, and fecundity was assessed through the number of oocytes by the gravimetric method. Body length and weight were 15.2 ± 1.9 cm and 68.5 ± 24.7 g respectively, and the weight of gonads was 12.5 ± 5.3 g. The estimate number of oocytes was 45 058 ± 20 770. The relative fecundity varied from 1194 to 6619 oocytes per cm of body length, from 302 to 1202 oocytes per gram of body weight, and from 2654 to 8739 oocytes per gram of gonad weight. The regression analysis showed that gonad weight is a suitable predictor of the fecundity in this species.